2016
DOI: 10.18632/oncotarget.8633
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1-mediated downregulation of COX2 restrains tumor growth caused by TSC2 deficiency

Abstract: Tuberous sclerosis complex (TSC), caused by loss-of-function mutations in the TSC1 or TSC2 gene, is characterized by benign tumor formation in multiple organs. Hyperactivation of mammalian target of rapamycin complex 1 (mTORC1) is the primary alteration underlying TSC tumors. By analyzing Tsc2-null mouse embryonic fibroblasts (MEFs) and rat uterine leiomyoma-derived Tsc2-null ELT3 cells, we detected evidence for the involvement of cyclooxygenase 2 (COX2) as a downstream target of mTORC1 in the development of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…The red pigment extracted from strain NJZT-1 were next determined by the high performance liquid chromatography coupled with mass spectrometry (HPLC-MS). Our results from the HPLC analysis showed that, the major product was eluted at 14.323 min ( Figure 4A), similar to the pervious investigation of prodigiosin (Li et al, 2016). Moreover, as shown in Figure 4B, there was a molecular ion peak M + H of prodigiosin at m/z 324, which corresponded to the molecular weight of prodigiosin (C 20 H 25 N 3 O, 323 kD).…”
Section: Strain Isolation and Product Extraction Charaterization Andsupporting
confidence: 87%
“…The red pigment extracted from strain NJZT-1 were next determined by the high performance liquid chromatography coupled with mass spectrometry (HPLC-MS). Our results from the HPLC analysis showed that, the major product was eluted at 14.323 min ( Figure 4A), similar to the pervious investigation of prodigiosin (Li et al, 2016). Moreover, as shown in Figure 4B, there was a molecular ion peak M + H of prodigiosin at m/z 324, which corresponded to the molecular weight of prodigiosin (C 20 H 25 N 3 O, 323 kD).…”
Section: Strain Isolation and Product Extraction Charaterization Andsupporting
confidence: 87%
“…MT-CO2 is usually unexpressed and has the characteristic of inducible expression. Once the transcript originates from MT-CO2 expression, it can induce tumour occurrence 50 and increase the probability of inducing tumour in females. 51 Moreover, fusion event could not only span two distinct genes but also produce variant isoforms with AS events.…”
Section: Resultsmentioning
confidence: 99%
“…Cell proliferation was measured by an MTT assay according to the manufacturer's instructions and has been described previously [ 29 ]. For the cell viability assays, Tsc1- or Tsc2-null MEFs were seeded in 96-well plates at a density of 3, 000 cells/well and treated with DMSO, rapamycin, AG1295, or combination of rapamycin and AG1295 for 48 h. Followed by added 10 μl of Cell Counting Kit-8 reagent (Beyotime, China) to per well and incubated the plates for 1 h, the optical density (OD value) of each well was measured at 450 nm.…”
Section: Methodsmentioning
confidence: 99%